Resolving Domination Number pada Keluarga Graf Buku - Quthrotul Aini Fuidah; Dafik Dafik; Ermita Rizki Albirri (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2020)
All graph in this paper are members of family of book graph. Let $G$ is a connnected graph, and let $W = \{w_1,w_2,...,w_i\}$ a set of vertices which is dominating the other vertices which are not element of $W$, and the elements of $W$ has a different representations, so $W$ is called resolving dominating set. The minimum cardinality of resolving dominating set is called resolving domination number, denoted by $γ_r(G)$. In this paper we obtain the exact values of resolving dominating for family of book graph.